2007
DOI: 10.1177/193229680700100104
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization Techniques to Avoid Enzyme Loss from Oxidase-Based Biosensors: A One-Year Study

Abstract: Background:Continuous amperometric sensors that measure glucose or lactate require a stable sensitivity, and glutaraldehyde crosslinking has been used widely to avoid enzyme loss. Nonetheless, little data is published on the effectiveness of enzyme immobilization with glutaraldehyde. Methods:A combination of electrochemical testing and spectrophotometric assays was used to study the relationship between enzyme shedding and the fabrication procedure. In addition, we studied the relationship between the glutaral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 23 publications
1
35
0
1
Order By: Relevance
“…9 Other studies have shown that, while glucose sensors loaded with excess GO x could extend sensor lifetime, 172 any excess free (un-cross linked) GO x originally entrapped within the glutaraldehyde cross-linked enzyme layer can slowly leach out and contribute to a decline in sensitivity over time. 168 These factors should be taken into consideration to extend long-term in vivo sensor life. Enzyme denaturation is another concern for long-term enzymatic decay.…”
Section: Enzyme Degradationmentioning
confidence: 99%
“…9 Other studies have shown that, while glucose sensors loaded with excess GO x could extend sensor lifetime, 172 any excess free (un-cross linked) GO x originally entrapped within the glutaraldehyde cross-linked enzyme layer can slowly leach out and contribute to a decline in sensitivity over time. 168 These factors should be taken into consideration to extend long-term in vivo sensor life. Enzyme denaturation is another concern for long-term enzymatic decay.…”
Section: Enzyme Degradationmentioning
confidence: 99%
“…31 Subsequently, the GO x enzyme was immobilized by dip coating the Pt/PPh electrode from a solution of 140 mg/ml GO x , 56 mg/ml BSA, and 25% weight/volume glutaraldehyde, the latter of which enables enzyme cross linking, followed by a 2 h soak in phosphate-buffered saline (PBS) to remove the uncrosslinked proteins. 32 The next step involved dip coating the sensor with a polyurethane (PU) layer from a 3% (weight/weight) PU solution in 98% tetrahydrofuran/2% dimethylformamide (weight/weight). 33 Subsequently, a thin layer of catalase enzyme was added by coating it with a solution of catalase, BSA, and glutaraldehyde, followed by another 2 h soak in PBS to remove the uncross-linked proteins.…”
Section: Coil-type Glucose Sensorsmentioning
confidence: 99%
“…This is due to the formation of proteins cross-linked by amino groups with strong azomethine (Fernandez-Lorente et al 2006;House et al 2007).…”
Section: Resultsmentioning
confidence: 99%